High-frequency spending responses to government transfer payments - Daniel Cooper; Giovanni P. Olivei (Federal Reserve Bank of Boston, 2021)
This paper evaluates the marginal propensity to consume (MPC) out of the 2020 fiscal stimulus payments using high-frequency, transaction-level data for a sample of low-income cardholders, many of whom are unbanked. Consumers' MPC out of non-stimulus income and their MPC out of tax refunds are estimated simultaneously. Spending responds less on impact to the stimulus payments than to non-stimulus income (15 cents versus 20 cents per dollar of income), but stimulus-payment spending quickly catches up and is noticeably higher than non-stimulus-income spending on a cumulative basis after 16 weeks (66 cents versus 46 cents). This finding is qualitatively quite robust, and there is relevant heterogeneity in the spending responses across cardholders that includes some pandemic-related effects.
Keywords: E21; 330; consumption; fiscal stimulus payments; tax rebates; marginal propensity to consume